Americanizing the Sulu Sultanate: Fragrance/Nightmare of U.S. Foreign Policy (circa 1898) - Michael Vincent P. Caceres (Philippine Association of Institutions for Research, Inc., 2012)
When the war broke out between Spain and the United States, the Spaniards had fought only with wooden ships against modern American warships. This event was known as the Battle of Manila where it made the United States a world super power. The Filipinos fought side by side with the Americans against Spanish colonialism. There was a sense of euphoria a certain scent of fragrance on the interference of the United States as a new player in the Asia Pacific region. When the Treaty of Paris was concluded between Spain and the United States on December 10, 1898 it finally gave the U.S. government an access to enter the Philippines. The presence of the Americans in Sulu was regarded as a new form of colonialism better known as imperialism in the modern age of West America. It affected the status of the sultanate and weakening the century old institution in the east. The coming of the Americans can be considered both as a form of blessing and cursed. The United States, represented by its military and civilian governors introduced policies that affected the entire Sultanate in almost its entire political facet. The paper looked into the strategic programs and designs that made their campaigned in Sulu either as a success or a failure coated with fragrance of promises on one side and nightmare on the other side.